Maternal docosahexaenoic acid supplementation during pregnancy and visual evoked potential development in term infants: a double blind, prospective, randomised trial. Issue 5 (1st September 2003) - Malcolm, C A; McCulloch, D L; Montgomery, C; Shepherd, A; Weaver, L T
Abstract : Aim: To test the hypothesis that maternal docosahexaenoic acid (DHA) supplementation during pregnancy enhances maturation of the visual evoked potential (VEP) in healthy term infants. Methods: One hundred women were supplemented with either fish oil capsules rich in DHA (n = 50) or placebo capsules (n = 50) from week 15 of pregnancy until delivery. Total fatty acids in red blood cells and plasma were measured at weeks 15, 28, and 40 of pregnancy and at delivery in umbilical cord blood. Infant visual pathway development was assessed using VEPs recorded to flash stimuli shortly after birth and to both flash and pattern-reversal stimuli at 50 and 66 weeks post-conceptional age (PCA). Results: Maternal supplementation did not significantly elevate the level of DHA in umbilical cord blood. Moreover, there were no significant differences in any of the VEP measures observed between supplementation groups. However, maturity of the pattern-reversal VEP at 50 and 66 weeks PCA was associated with DHA status of the infants at birth. Infants with higher DHA status, both as a concentration and as a percentage of total fatty acids, showed shorter P100 peak latencies of the pattern-reversal VEP than those with lower DHA status. Conclusions: Maternal DHA supplementation during pregnancy did not enhance VEP maturation in healthy term infants. However, these results show an association between the DHA status of infants at term and early postnatal development of the pattern-reversal VEP, suggesting that DHA status itself may influence maturation of the central visual pathways.